O princípio constitucional da fraternidade no direito penal brasileiro : avanços legislativos e jurisprudenciais - Santos, Francisco Gerlandio Gomes dos (2021)
The study demonstrates the aprioristic application of the Principle of Fraternity in Brazilian Criminal Law, and aims to point out that the institute substantiates modern criminal rationality, by ensuring the criminal protection of legal assets essential to harmonious collective coexistence, while neutralizing the State's punitive excesses. Therefore, an inductive phenomenological methodology is adopted: from the analysis of legislative and jurisprudential innovations in Brazil, the repercussions of these measures in the sphere of rights of those affected are focused. The research methodology is not reproduced in the presentation of the study. It began with the exposition of the evolutionary framework of the Principle, demonstrating that the ideal of Fraternity is common to the Hellenes and older Christians, showing that both in the philosophical spectrum and in the religious sphere, the unfolding of the Principle already foreshadowed its humanely inclusive nature, which was maintained, if not perfected, by the political contour given in the French Revolution. It was observed, however, that the politicization of the institute does not unusually coincide with the same densification given to the other bases of the revolutionary triad – Equality, Liberty and Fraternity. Next, an analysis of the Federal Constitution of the Federative Republic of Brazil, of October 5, 1988, and taking into account the decision of the Supreme Court discussed below, it is demonstrated that the evocation of the Fraternity in the Preamble of the Charter transcends the statements of the higher normative body, being the foundation of social development. Having revealed some constitutional provisions that are essentially fraternal, it was found that, among these provisions, there are some of immediate application in the field of Criminal Law, thus including not only the materially punitive provisions, but also the essentially procedural and criminal enforcement rules , since, as the doctrine adopted in the work points out, it is necessary to understand the dynamics of the jus puniendi as a sequence of sanctioning state acts, limited by human dignity, which should guide from the choices of legal goods recipients of criminal protection, to the rules proceduralists and the execution of the legitimate penalty. Combining the infra-constitutional legislation and the jurisprudence of the Superior Courts, these institutes are compared with the theoretical basis of the principle, and an attempt is made to answer the following questions: is it possible to increase the incidence of the fraternity principle in the area of Criminal Law? Does its incidence lead to the implementation of rights and guarantees? Does it serve as a basis for the selection of legal assets for criminal protection? In conclusion, it is inductively pointed out the positive answer to each of the questions, while it is revealed that, a contrario sensu, the neglect of this legal-hermeneutic load results in what we will call punishments-obstacles to social development.